Risk factors for the increasing trend in low birth weight among live births born by vaginal delivery, Brazil - Barbieri Marco A; Silva Antônio AM; Bettiol Heloisa; Gomes Uilho A (Universidade de São Paulo, 2000)
OBJECTIVE: To identify risk factors for low birth weight (LBW) among live births by vaginal delivery and to determine if the disappearance of the association between LBW and socioeconomic factors was due to confounding by cesarean section. METHODS: Data were obtained from two population-based cohorts of singleton live births in Ribeirão Preto, Southeastern Brazil. The first one comprised 4,698 newborns from June 1978 to May 1979 and the second included 1,399 infants born from May to August 1994. The risks for LBW were tested in a logistic model, including the interaction of the year of survey and all independent variables under analysis. RESULTS: The incidence of LBW among vaginal deliveries increased from 7.8% in 1978--79 to 10% in 1994. The risk was higher for: female or preterm infants; newborns of non-cohabiting mothers; newborns whose mothers had fewer prenatal visits or few years of education; first-born infants; and those who had smoking mothers. The interaction of the year of survey with gestational age indicated that the risk of LBW among preterm infants fell from 17.75 to 8.71 in 15 years. The mean birth weight decreased more significantly among newborns from qualified families, who also had the highest increase in preterm birth and non-cohabitation. CONCLUSIONS: LBW among vaginal deliveries increased mainly due to a rise in the proportion of preterm births and non-cohabiting mothers. The association between cesarean section and LBW tended to cover up socioeconomic differences in the likelihood of LBW. When vaginal deliveries were analyzed independently, these socioeconomic differences come up again.